Political Dinamism of Islam In The Modern Age (Political Thinking Analysis of Muhammad Iqbal) - Maulana Azri Ba’dawi; Junaidi, Junaidi; Jufri Naldo (Dinasti Research, 2024)
Islam is often preached with rigid stigma and is not flexible. This view is confusing, because throughout its history Islam has expressed a dynamic nature in responding to the development of the times. One example is the political thinking of Muhammad Iqbal. This research aims to investigate the ideas of Muhammad Iqbal about the Islamic state concept of democracy and nationalism to express the dynamic pattern of modern Islamic political thought. The focus of this research is how the pattern of the dynamism of Islamic political thinking in the modern era is described in the works of Muhammad Iqbal, in particular in the book “The Reconstruction of Religious Thought in Islam”. The research uses qualitative methods with content analysis approach to analyze the political thinking of Muhammad iqbal. The results of this study indicate that Muhammad Iqbal made a creative and contextual interpretation of the teachings of Islam to describe political theories appropriate to his time. In conclusion, the political thought of Muhammad Iqbal describes the concept of modern Islamic political dynamism which is contextual, progressive, and inspiring for the resurrection of contemporary Islam.